THE THEME OF SUFFERING IN THE WORKS OF FYODOR DOSTOEVSKY (Bulletin of Innovative Research, 2026)
This article examines the specifics of the guilt motif and its connection with suffering in the novels of F.M. Dostoevsky. Suffering is viewed as a natural consequence of guilt and simultaneously as a path to spiritual rebirth. It is shown that guilt in Dostoevsky is not only a legal or moral category, but, above all, an ontological state of a person.